Sosialisasi Aplikasi Web “Srigading Sehat” sebagai Upaya Peningkatan Akses Informasi Kesehatan melalui Pendekatan IDEA - Mohamad Tegar Deyustianmuslim; Amala Mulyasari; Fa’iq Zhafran Naufal Brinata; Joko Muliyono; Abdul Azis; Annisya Annisya (Universitas Muhammadiyah Manado, 2025)
Public health is a crucial aspect of improving well-being, particularly at the village level. However, in Srigading Village, Lawang District, Malang Regency, access to information related to health services remains a significant challenge, resulting in suboptimal utilization of Posyandu and Puskesmas services. To address this issue, a web application called “Srigading Sehat” has been developed as a digital platform providing health service information through interactive maps and service schedules. This community service activity employs the IDEA approach (Identify Objective, Design Action Steps, Engage Our Plan, Assess and Follow Up) as a systematic framework. The Identify Objective stage identified limitations in health information access; Design Action Steps designed a participatory learning-based application development model; Engage Our Plan implemented application development, socialization, and training for 25 participants comprising village officials, posyandu cadres, and the general community; and Assess and Follow Up evaluated achievements through Firebase Analytics monitoring. Results showed increased health information access marked by 500 health information page visits within the first 30 days of launch, with total Firebase reads reaching 631 (+1,026.8%). Four village health facilities are actively registered and using the application to independently update their service information. This application is anticipated to serve as an appropriate technological innovation contributing to the enhancement of health services at the village level.